2015
DOI: 10.1016/j.bbmt.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplant High-Dose Cyclophosphamide for the Prevention of Graft-versus-Host Disease

Abstract: Cyclophosphamide's lack of hematopoietic stem cell toxicity and its unique effects on the immune system have prompted several investigators to explore its potential for the prevention of graft-versus-host disease (GVHD). In haploidentical hematopoietic stem cell transplants, post-transplant cyclophosphamide together with standard prophylaxis reduces the incidence of GVHD to acceptable rates without the need for T cell depletion. In matched related and unrelated donor settings, cyclophosphamide alone has produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 43 publications
(50 reference statements)
0
77
0
1
Order By: Relevance
“…High doses of cyclophosphamide and sirolimus have been successfully used to prevent GVHD and have been shown to enhance the activity of Treg cells. [85][86][87] Although early studies have suggested a negative effect of cyclophosphamide on Treg cells, the role of Treg cells in the cyclophosphamide GVHD prophylactic effect, is essential. In the xenogenic GVHD mouse model, Kanakry and colleagues proved that when peripheral blood mononuclear cell grafts were depleted of Tregs, the humanized mice had severe GVHD scores and died earlier, and suggested the requirement of Treg cells for the optimal effect of cyclophosphamide.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
“…High doses of cyclophosphamide and sirolimus have been successfully used to prevent GVHD and have been shown to enhance the activity of Treg cells. [85][86][87] Although early studies have suggested a negative effect of cyclophosphamide on Treg cells, the role of Treg cells in the cyclophosphamide GVHD prophylactic effect, is essential. In the xenogenic GVHD mouse model, Kanakry and colleagues proved that when peripheral blood mononuclear cell grafts were depleted of Tregs, the humanized mice had severe GVHD scores and died earlier, and suggested the requirement of Treg cells for the optimal effect of cyclophosphamide.…”
Section: Mechanisms Underlying the Suppressive Function Of Foxp3 1 Trmentioning
confidence: 99%
“…Novel strategies of prevention GVHD may be more effective as compared to treatment of acute or chronic GVHD. Recent trials with the use of post-transplant cyclophosphamide in unrelated donor transplant have shown mixed results [167], but it was shown to be very effective in haploidentical donor HSCT. Inducible caspase 9 (iC9) suicide gene expressing T cells have been used to decrease incidence of GVHD and improve immune reconstitution and has shown promising results [168].…”
Section: Future Directionsmentioning
confidence: 99%
“…Whether early donor lymphocyte infusion after T-cell depleting strategies or high-dose cyclophosphamide post transplant counterbalance NRM versus relapse is the subject of much debate and investigation. 15,16 Chronic GvHD reduced the chance of relapse in many studies; however, in a recent registry study of the Center for International Blood and Marrow Transplant Research (CIBMTR), its impact seemed only clinically relevant for CML after myeloablative alloSCT and not for AML. 17 In this study, cGvHD was primarily associated with a higher transplant-related mortality (TRM).…”
Section: Transplant-related Factors In Relation To Relapse Risk Aftermentioning
confidence: 99%